Language Network Function in Young Children Born Very Preterm - Choi, Eun Jung; Vandewouw, Marlee M.; Young, Julia M.; Taylor, Margot J. (Frontiers in Human Neuroscience, 2018)
Language deficits are reported in preterm born children across development. Recent neuroimaging studies have found functional alterations in large-scale brain networks underlying these language deficits, but the early childhood development of language network has not been investigated. Here, we compared intrinsic language network connectivity in 4-year-old children born VPT and their term-born controls, using defined language regions (Broca’s area, Wernicke’s areas, and their homologues in the right hemisphere). Resting-state functional magnetic resonance imaging (fMRI) was obtained, and the group differences in whole-brain connectivity were examined from each seed as well as correlations with language outcomes. We found significantly decreased functional connectivity in almost all language regions in children born VPT compared to their term controls. Notably, Broca’s area homologue in the right hemisphere emerged as a functional hub of decreased connectivity in VPT group, specifically to bilateral inferior frontal and supramarginal gyri; the connectivity strength between Broca’s area homologue with the right supramarginal and the left inferior frontal gyri was associated with better language outcomes at 4 years of age. Wernicke’s area and its homologue also showed decreased inter-hemispheric connections to bilateral supramarginal gyri in VPT group. Decreased intra- and inter-hemispheric connectivity among primary language regions suggest immature and altered function in the language network in children born VPT.